TAJIKISTAN-CHINA: TWENTY-FIVE YEARS OF DIRECT RELATIONS - ABDULLO, Rashid (CENTRAL ASIA AND THE CAUCASUS, 2015)
This article analyzes Tajikistan’s relations with the People’s Republic of China (PRC) in the almost twenty-five years since direct and broad relations were restored between the two countries in the context of two overlapping trends. One of them is the striving of the Tajik leadership to acquire a reliable source of foreign funding for the republic’s economic development in light of its own extremely limited financial resources. The second is the consistent implementation by the Chinese leadership of reciprocal economic-political strategies—the New Silk Road, Going Out, and the Silk Road Economic Belt. Implementation of the first two strategies restored direct economic relations between the two countries, made it possible for Tajikistan to carry out several of its strategic infrastructural projects, turned China into Tajikistan’s strategic political and economic partner and gave the PRC direct access to Tajikistan’s raw materials, particularly mining resources. At that, implementation of the first of the Chinese strategies, the New Silk Road, raised employment in Tajikistan, saturated its market with cheap Chinese consumer goods, and, consequently, promoted social stability. Implementation of the third strategy is fortifying China’s status as Tajikistan’s strategic partner even more. Nevertheless, China’s stronger position in the republic is fraught with substantial risks, the main one being the lack of a practical alternative to the Republic’s broad economic cooperation with its great Eastern neighbor. Tajikistan must continue to follow a multisectoral course, not only in its strictly political, but also in its economic relations with the outside world in order to avoid unilateral dependence on its strategic partner.